Intracanal Adaptation of a Fiber Reinforced Post System as Compared to a Cast Post-and-Core - Nor Aidaniza Abdul Muttlib; Aimi Najwa Pahrol Azman; Yee Tong Seng; Rabihah Alawi; Zaihan Ariffin (University of Zagreb. School of Dental Medicine, 2016)
Background: The purpose of this study was to compare the adaptation of fiber reinforced composite post system and cast post-and-core. Methods: 17 extracted human permanent maxillary central incisors were endodontically treated following the standard protocol. 17 fiber reinforced composite post had been fabricated and adapted to the prepared parallel root canals. A light body poly vinyl siloxane (EXAMIX NDS, Japan) impression material was inserted into the root canals followed by the post. A digital scale was used to measure the weight of the remaining material that filled the gap between the post and the canal wall. The adaptation was indicated by the weight difference before and after impression material insertion. The same procedures were repeated with 17 cast post-and-core in the same teeth specimens. Result: The mean difference for the weight of the material within the group was statistically significant (P-value <0.001) with the value of 6.1mg(± 2.7mg) for cast metal post and 6.4mg(± 2.7mg) for fiber reinforced composite post. However, the mean difference was not statistically significant when compared with both materials (P-value>0.05). Conclusions: Both cast post-and-core and fiber reinforced composite post systems showed similar adaptation to the canal.